Serie de Fourier - Arriola-Valverde, Sergio; Coto-Cortés, Aníbal (My University, 2017)
La unidad contiene todos los subtemas a tratar a lo largo de 16 semanas de curso. Se divide en 5 partes que contienen ejercicios, animaciones, imágenes, teoría y lecturas recomendadas. Se analiza la forma trigonométrica de la serie de Fourier, su simetría, forma compleja y espectro, así como el circuito y serie de Fourier.

This unit has all the necessary sub-topics over the 16 weeks' course. It is divided into 5 parts containing proposed exercises, animations, images, theory and recommended readings. The trigonometric form of the Fourier series, its symmetry, complex form and spectrum, as well as the circuit and Fourier series are analyzed.
Keywords: Series de fourier; Simetría; Circuitos; Ondas; Movimientos ondulatorios; Funciones; Symmetry; Circuits; Waves; Functions